UZBEK STUDENTS’ PERCEPTION OF AI TOOLS FOR IMPROVING LISTENING SKILLS: A MIXED-METHODS STUDY - Baxramova Malika Muzaffarovna (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: The increasing integration of Artificial Intelligence (AI) technologies in language education has introduced new opportunities for enhancing listening comprehension skills. This mixed-methods study explores the perceptions of Uzbek university students regarding the effectiveness, usability, and pedagogical value of AI tools in improving English listening skills. Quantitative data were collected through structured surveys involving over 150 undergraduate students from three higher education institutions, while qualitative insights were gathered from semi-structured interviews with a smaller subgroup. The findings reveal a generally positive perception of AI tools, with students appreciating features such as personalized feedback, repeatable audio playback, and adaptive difficulty levels. However, challenges were also reported, including technical barriers, unfamiliarity with some tools, and the limitations of synthetic audio content. Many students expressed a preference for a blended learning approach where AI supports, but does not replace, human instruction. The study emphasizes the importance of accessible digital infrastructure, instructor guidance, and culturally appropriate content to optimize the use of AI in listening pedagogy. The results suggest that, when thoughtfully integrated, AI technologies can significantly enhance listening skill development and learner autonomy in the Uzbek context.